Altered Spatiotemporal Expression of Collagen Types I, III, IV, and VI in Lpar3-Deficient Peri-Implantation Mouse Uterus - Diao, Honglu (Society for the Study of Reproduction, Inc., 2010)
Lpar3 is upregulated in the preimplantation uterus, and deletion of Lpar3 leads to delayed uterine receptivity in mice. Microarray analysis revealed that there was higher expression of Col3a1 and Col6a3 in the Preimplantation Day 3.5 Lpar3(−/−) uterus compared to Day 3.5 wild-type (WT) uterus. Since extracellular matrix (ECM) remodeling is indispensable during embryo implantation, and dynamic spatiotemporal alteration of specific collagen types is part of this process, this study aimed to characterize the expression of four main uterine collagen types: fibril-forming collagen (COL) I and COL III, basement membrane COL IV, and microfibrillar COL VI in the peri-implantation WT and Lpar3(−/−) uterus. An observed delay of COL III and COL VI clearance in the Lpar3(−/−) uterus may be associated with higher preimplantation expression of Col3a1 and Col6a3. There was also delayed clearance of COL I and delayed deposition of COL IV in the decidual zone in the Lpar3(−/−) uterus. These changes were different from the effects of 17beta-estradiol and progesterone on uterine collagen expression in ovariectomized WT uterus, indicating that the altered collagen expression in Lpar3(−/−) uterus is unlikely to be a result of alterations in ovarian hormones. Decreased expression of several genes encoding matrix-degrading metallo- and serine proteinases was observed in the Lpar3(−/−) uterus. These results demonstrate that pathways downstream of LPA3 are involved in the dynamic remodeling of ECM in the peri-implantation uterus.